2012
DOI: 10.5301/ejo.5000220
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors to Develop Ocular Surface Disease in Treated Glaucoma or Ocular Hypertension Patients

Abstract: There is clinical evidence that the number of medications, their prolonged use, and the total BAK exposure are risk factors to develop OSD in patients with glaucoma. To prevent OSD onset, BAK exposure and the number of topical medications should be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 17 publications
2
76
0
1
Order By: Relevance
“…A significant increase in the prevalence of OSD signs was observed in the glaucoma population, 70.3%, compared to controls, 33% [21]. Studies have demonstrated the possibility that interaction between glaucoma and OSD syndrome increases because of topical ocular medications [5,8,22]. Once applied, any topical medication exerts toxicity on ocular surface from the active compound.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A significant increase in the prevalence of OSD signs was observed in the glaucoma population, 70.3%, compared to controls, 33% [21]. Studies have demonstrated the possibility that interaction between glaucoma and OSD syndrome increases because of topical ocular medications [5,8,22]. Once applied, any topical medication exerts toxicity on ocular surface from the active compound.…”
Section: Discussionmentioning
confidence: 97%
“…Patients were grouped into 4 categories by OSDI score: normal (scores 0-12), mild OSD symptoms (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate OSD symptoms (23-32), severe OSD symptoms (33-100) [13]. Patients' medical records were used to obtain medical history including detailed data on the use of medication and duration of therapy.…”
Section: Clinical and Experimental Ophthalmologymentioning
confidence: 99%
“…Надо отметить что, несмотря на отсутствие консерванта в препарате Тафлу-прост, при его применении наблюдалась гиперемия конъ-юнктивы [14,15,16,17,18]. Можно предположить, что ги-перемия связана с активным действием простагландинов, как медиаторов воспаления и аллергических реакций, независимо от наличия или отсутствия консервантов в составе препарата [19,20,21,22,23,24]. Изменение пигмен-тации радужки у 5 пациентов первой группы и 6 второй, усиление роста и потемнение ресниц на 12 неделе отме-чено у всех пациентов обеих групп.…”
Section: результаты и обсуждениеunclassified
“…Various observational studies conducted in recent years in Europe and the US have shown a consistent prevalence of OSD in glaucoma of approximately 50 % (range: 40 %-60 %) [1][2][3][4][5] with 27 % of patients suffering from severe OSD (see Figure 1). …”
mentioning
confidence: 91%
“…1,[3][4][5][6][7] This association was emphasised in one study on 101 patients in the US showing that each additional BAK-containing eye drop administered was associated with approximately twofold higher odds of abnormal results on the lissamine green staining test. 4 A recent study of 516 patients with glaucoma in France found that the disease could be divided into three groupings in terms of OSD: Group A who were considered normal (score 1-4, 49 %), Group B who were mild to moderate (score 5-10, 30 %) and Group C who were severe (score 11-30, 21 %).…”
mentioning
confidence: 99%